The Rapid Writing Strategy in Writing Classroom during the Covid-19 Pandemic - Hidayah, Nurul; Hafidz, Moh; Kiptiyah, Mariyatul (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2022)
Writing skill is an ability to share an idea in written text based on the genre of the text, the rapid writing strategy is one of appropriate strategy to make a good paragraph especially in descriptive text because most of the participants are from rural area and different writing achievements. The aim of this research is to investigate the procedure of the rapid writing strategy behaves in the teaching-learning of writing skill. Researcher descriptively used the qualitative method that specifically uses a case study design by observing the field via Whats App platform. The instrument of this research is observation checklist and taking notes to get a complete data either from personal or group Whats App. The teacher and students activities inside and outside the class becomes a primary source of data. Results, the rapid writing strategy is a fast writing practice strategy without paying attention to what has been written in advance so that writing is completed quickly and completely the rapid writing strategy helps students explore writing more without worrying about grammatical accuracy, content and vocabulary for students to do tasks in descriptive text. In addition, this strategy makes teachers more motivated, interested and fun in teaching-learning process of writing skill. Keywords: Writing, rapid strategy, teaching-learning, descriptive text.Writing skill is an ability to share an idea in written text based on the genre of the text, the rapid writing strategy is one of appropriate strategy to make a good paragraph especially in descriptive text because most of the participants are from rural areas and different writing achievements. The aim of this research is to investigate the procedure of the rapid writing strategy behaves in the teaching-learning of writing skills. The researcher descriptively used the qualitative method that specifically uses a case study design by observing the field via Whats App platform. The instrument of this research is an observation checklist and taking notes to get complete data either from personal or group Whats App. The teacher and students' activities inside and outside the class become a primary source of data. Results, the rapid writing strategy is a fast writing practice strategy without paying attention to what has been written in advance so that writing is completed quickly and completely the rapid writing strategy helps students explore writing more without worrying about grammatical accuracy, content, and vocabulary for students to do tasks in descriptive text. In addition, this strategy makes teachers more motivated, interested, and fun in the teaching-learning process of writing skills.